Методи та засоби зниження невизначеностей оцінювання інтенсивності теплообміну в складних сумішах - Ткаченко, С. Й.; Пішеніна, Н. В.; Румянцева, Т. Ю. (НТУ "ХПИ", 2014)
З метою зниження невизначеностей оцінювання інтенсивності теплообміну в складних сумішах виконано дослідження експериментально-розрахункового методу (ЕРМ) визначення інтенсивності теплообміну між металевою стінкою і складними сумішами, для яких інформація про теплофізичні властивості не відома. Удосконалено експериментальну і розрахункову частини ЕРМ. В експериментальному стенді ЕРМ добавлена установка для визначення інтенсивності за умов вимушеного руху. Забезпечено експериментальне визначення розподілу температур по висоті грійного і нагріваного теплоносія. З метою автоматизації збору та обробки експериментальна інформація виводилась на комп’ютер. Удосконалено метод обробки експериментів шляхом уточнення діапазону параметрів проведення досліджень. Запропоновано і введено в систему ЕРМ метод визначення належності натурної суміші (розчину) до ньютонівських або неньютонівських рідин. Вперше запропоновано і науково обґрунтовано методи вибору «модельної» та «частково-модельної рідини» у конкретних теплогідродинамічних умовах та застосування їх теплофізичних властивостей для оцінювання інтенсивності теплообміну в складних сумішах в елементах натурного обладнання.

To reduce the uncertainties of the estimation of the heat exchange intensity in compound mixtures we studied the experimental-&-design method (EDM) used for the determination of the heat exchange intensity between the metal wall and the compound mixtures, whose thermal and physical properties-related information is unknown. The experimental and design component of the EDM has been improved. The experimental unit was added to the experimental bench used for the realization of the EDM to determine the intensity in the conditions of forced motion. The experimental determination of the temperature distribution along the height of heating and heated thermal carriers has been provided. To provide computer-aided data collection and processing the experimental information was keyboarded into the computer. A method of the processing of experiments by specifying the parameter range for the studies has been proposed. The method used for the determination of the type of liquids (Newtonian or non-Newtonian) to which the natural mixture (solution) is attributed was proposed and introduced into the EDM system. The methods of the selection of the "model" and "partially model liquid" in definite hydrodynamic conditions and the use of thermal and physical properties for the estimation of the heat exchange intensity in compound mixtures in full-scale equipment elements have been proposed and scientifically substantiated.
Methods and tools used for the reduction of the uncertainty of the estimation of the heat exchange intensity in compound mixtures
Keywords: експериментально-розрахунковий метод; неньютонівська рідина; теплофізичні властивості; heat exchange; experimental-&-design method; compound mixture; non-Newtonian liquid; thermal; physical properties